Degradability and estimation of the intake of forages and concentrates in alpacas (Vicugna pacos) - Cordero F., Alfonso (2018)
The objective of the study was to evaluate the kinetic parameters of in situ degradation of dry matter (DM), crude protein (PC) and the estimation of DM intake of forages and concentrated feeds by prediction equations in Huacaya alpacas (Vicugna pacos). The study included maize silage (Zea mays L) without and with 1% urea, barley (Hordeum vulgare L), oats (Avena sativa L), wheat bran (Triticum aestivum L) and potato scrap (Solanum tuberosum). The feeds (5 g on dry basis) were placed in nylon bags and incubated during 0, 6, 12, 24, 48 and 76 hours in the first stomach compartment of two fistulated alpacas. The MS and the PC of the residues in the nylon bags were analyzed. The DM and PC of wheat bran and potato scrap showed high degradation potential, as well as MS and PC of oats. The highest non-degradable fraction of the PC of the maize with and without urea is highlighted and, therefore, PC showed lower degradability. Estimates of consumption by alpacas generated by the equations of three studies are not adequate for the feeds under study.